THINK-TALK-WRITE (TTW) AS A STRATEGY TO IMPROVE STUDENTS’ ABILITY IN TEACHING WRITING DESCRIPTIVE TEXT: A CASE OF THE TENTH GRADE STUDENTS OF MAN DEMAK - Wiyak Wiyak; Irpan Subhan Ansori (ETERNAL (English Teaching Journal), 2013)
This study focuses on Think-Talk-Write Strategy in teaching descriptive text to improve students’ writing ability. The objectives of this study are (1) to find out the students’ writing ability of the tenth grade students of MAN Demak in academic year 2014/2015 who were taught by using Think-Talk-Write (TTW). (2) to find out the students’ writing ability of the tenth grade students of MAN Demak in academic year 2014/2015 who were taught without using Think-Talk-Write (TTW). (3) to find out whether or not there was a significant difference of writing ability between the tenth grade students of MAN Demak in academic year 2014/2015 who were taught with Think-Talk-Write (TTW) strategy and without Think-Talk-Write (TTW). The research was Quasi-Experimental research. The subject of the study was the tenth grade students of MAN Demak. Cluster sampling is used in taking the sample. 40 students from class X-5 were selected as the experiment group and 40 students from class X-1 as the control group. The t-test was used to analyze the data. Experiment research was used here to get the data. The pre-test was given to the students on both of groups. After that, the difference treatment was given in experimental group. At the end of the research, the post-test was given to both of groups. The count of the mean score of the experimental class was 79.95 and the count of mean score of the control class was 76.17. It shows that teaching descriptive text by using Think-Talk-Write (TTW) Strategy gave better result as indicated significant statistical t-test computation, that the t-table value (t5% = 2.03 and t1% = 2.80) is less than t0 = 13.09 (2.03<13.09>2.80). It could be seen that there is a significant difference in writing ability of the tenth grade students of MAN Demak after being taught using Think-Talk-Write (TTW) Strategy. The researcher offers some suggestions in this research. The school should give good facilities and many strategies for teaching and learning process. For the teacher, the teacher should give variation teaching especially using new techniques and strategies in teaching descriptive text to improve students’ writing ability. For the students, the students have to do more active, confident and creative.